Estimating soil organic carbon storage and distribution in a catchment of Loess Plateau, China - Han, Fengpeng; Hu, Wei; Zheng, Jiyong; Du, Feng; Zhang, Xingchang (Geoderma, 2010)
Using soil as a carbon sink to sequester carbon dioxide has attracted much attention. But there is little research on soil organic carbon (SOC) in the Loess Plateau because of the extremely complex topography. In this study, SOC storage was estimated based on a soil survey of a small catchment in the Loess Plateau, northwest China. The SOC content of 169 profiles and the bulk density of 12 profiles were measured. The study area was classified into six different classes: farmland, grassland, shrub land, woodland, gully, Aeolian sandy soil. Results showed that the soil bulk density and SOC content are affected by land use and soil types, and the relationship between them could be expressed by a power function. Grassland had the highest SOC density, and next came farmland. Gully and Aeolian sandy soil had the lowest SOC density. The SOC content per area in the grassland and farmland was higher than the other classes and the shrub land was similar to the woodland while the Aeolian sandy soil and gully were the lowest. All of the changes in the cumulative SOC storage with the increasing depth follows a logarithmic model. The SOC storage in the catchment of farmland, grassland, shrub land, woodland, gully, and Aeolian sandy soil was estimated as 3.32 × 10 6 kg, 9.45 × 10 6 kg, 1.023 × 10 7 kg, 2.73 × 10 6 kg, 5.76 × 10 6 kg, and 2.94 × 10 6 kg, respectively. The total SOC storage of 100 cm depth in the catchment is 3.443 × 10 7 kg.